Modern Islamic Civilization in South and Southeast Asia - Nuraisah, Nuraisah; Permata, Yufi; Tabroni, Imam; Kathryn, Morse; Cale, Woolnough (International Journal of Educational Narratives, 2023)
Background. Islam is the second largest religion in South Asia, with more than 600 million Muslims living there, making up about a third of the region's population. The history of Islam in South Asia began along the coastal regions of the Indian subcontinent and Sri Lanka, after its beginnings in the Arabian Peninsula. Purpose. This research was made to thoroughly explore the history of Islamic civilization in the modern era in South Asia and Southeast Asia. With this research, it is hoped that it can add insight to the readers in the study of the history of Islamic civilization and can answer various questions about when Islam entered South Asia and Southeast Asia, how the process and impact on the people who live there, and who plays an important role in the spread of Islam on both continents. Method. The data collected will be analyzed by identifying the themes, arguments or main ideas in the texts and analyzing how they influenced and were influenced by the development of Islamic civilization in Southeast and South Asia. Results. Southeast Asia is home to the largest Muslim population in the world. Islam is the majority religion in Indonesia, Malaysia and Brunei Darussalam. Islam in Southeast Asia was spread through the activities of traders and Sufis. Unlike other Islamic regions of the world, it was spread through the Arab and Turkish conquests. Conclusion. Thus the presentation of material about Islamic Civilization in Southeast Asia and South Asia and how the method of its spread. We as writers realize that the results of the papers we compile are far from perfect, for the future we will try to be even better in presenting writing or discussion.